(untitled) (Journal of Universal Excellence, 2026)
Research question: How frequently pensioners use tourist offers as part of organised leisure activities of societies of pensioners, and what are their motifs for this? Aim: We want to find out, how are organised leisure activities and whether exist enough tourist offers for pensioners with regard to their financial situation and obstacles they face. Methods: We conducted research among Slovenian societies of pensioners. We conducted online survey which took place from 15 April to 15 July 2018. To increase responsiveness which was very low in the first stage of the survey, we added phone survey which was conducted by students of the School of advanced social studies. Results: Societies of pensioners organise many leisure activities. In a segment of tourist trips they prefer day trips around Slovenian. Due to limited finances a crucial factor in choosing accomodation is its price, while pensioners put much less attention on the classification of accomodation. Organisation: Findings of the research are relevant for tourist organisations and societies of pensioners. They enable tourist organisations to adapt their offers. Societies of pensioners have an option to co-operate in organising leisure activities and optimise their work. Society: Our contribution is important from a perspective of ageing society. Namely, a share of older persons increases, what evokes a need to manage also their leisure activities which include also tourist activities. Originality: It is the first so comprehensive survey conducted among Slovenian societies of pensioners which looked for answers with regard to organising tourist trips and motifs of pensioners to participate in them. Limitations of research: Limitation of research is reflected in a fact, that it included only heads of societies of pensioners. For a comprehensive view we should form some focus groups in selected societies of pensioners, as well as directly ask their members for their opinions. Furthermore, the research does not cover pensioners who are not active in societies.